New species and new records of linyphiid spiders from the Indo-Malayan Region (Araneae, Linyphiidae) - Tanasevitch, Andrei V. (Zootaxa, 2017)
Linyphiid spiders collected from the Indo-Malayan Region and kept at three European Museums are studied. Twenty-three known species are newly recorded from continental or insular parts of Southeastern Asia and from the Oriental area of India. Seven new species are described: Asiagone komannai n. sp. (from Thailand), Erigone apophysalis n. sp. and E. sumatrana n. sp. (Sumatra, Indonesia), Gnathonarium luzon n. sp. (Philippines), Ketambea acuta n. sp. (Thailand, Myanmar), Oedothorax myanmar n. sp. (Myanmar) and Theoa malaya n. sp. (West Malaysia).